2017
DOI: 10.1158/1078-0432.ccr-16-0947
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer OMIC Data in Medullary Thyroid Carcinoma Identifies the STAT3 Pathway as a Potential Therapeutic Target in RETM918T Tumors

Abstract: Medullary thyroid carcinoma (MTC) is a rare disease with few genetic drivers, and the etiology specific to each known susceptibility mutation remains unknown. Exploiting multilayer genomic data, we focused our interest on the role of aberrant DNA methylation in MTC development. We performed genome-wide DNA methylation profiling assessing more than 27,000 CpGs in the largest MTC series reported to date, comprising 48 molecularly characterized tumors. mRNA and miRNA expression data were available for 33 and 31 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
(71 reference statements)
2
16
0
Order By: Relevance
“…Combined incubation with RET and mTOR inhibitors (AST487 and INK128, respectively) at low concentrations cooperated to inhibit mTOR signaling and cell growth, through the induction of apoptosis, in both MTC cell lines. In addition, a recent study found that methylation profiles relate closely to RET mutational status in MTC, and the most distinctive methylome was observed for RET‐M918T‐positive tumors (Mancikova et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined incubation with RET and mTOR inhibitors (AST487 and INK128, respectively) at low concentrations cooperated to inhibit mTOR signaling and cell growth, through the induction of apoptosis, in both MTC cell lines. In addition, a recent study found that methylation profiles relate closely to RET mutational status in MTC, and the most distinctive methylome was observed for RET‐M918T‐positive tumors (Mancikova et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Integration of methylation and miRNA expression data from MTC samples carrying RET M918T mutation, showed that miR-10a, miR-30a, and-200c expression levels were negatively correlated with their promoters' methylation. Pathway enrichment analyses of these miRNAs uncovered JAK/Stat pathway involvement in RET M918T MTCs (Mancikova, et al, 2017).…”
Section: Mirnas In Mtc Formalin-fixed Paraffin-embedded (Ffpe) and Frmentioning
confidence: 99%
“…These data are in line with gene expression results by Ameur et al [paragraph 7. Genetic landscape of germline and somatic mutations in MTC] (Ameur, et al, 2009) and suggested that methylation profile relates to RET mutational status (Mancikova, et al, 2017). Although TERT mutations were not identified in MTC (Bae, et al, 2016;Romei, et al, 2016) , telomerase activation was detected in approximately 50% of sMTCs (Liu, et al, 2014).…”
Section: Dna Methylation In Mtc Formalin-fixed Paraffin-embedded (Ffpmentioning
confidence: 99%
See 2 more Smart Citations